Nutrition Management on Acute Pancreatitis - Ralph Girson Gunarsa; Rino Alvani Gani; Ari Fahrial Syam (The Indonesian Society for Digestive Endoscopy, 2007)
Pancreatitis is an inflammatory process in pancreas. Clinical manifestation of acute pancreatitis can be mild to severe. Mortality rate is high in severe acute pancreatitis. Etiology of acute pancreatitis generally remains obscured. Supportive management is important in acute pancreatitis. Nutrition is important part in acute pancreatitis. Patient should not be given enteral nutrition temporarily and meanwhile parenteral nutrition must provide sufficient amount of calories and nutritional requirements. Immune nutrition should also be considered. In mild acute pancreatitis, oral realimentation can be started in 3rd-7th day. In severe acute pancreatitis with prolonged fasting, gradual enteral nutrition via nasoenteral tube is recommended Keywords: nutrition, acute pancreatitis, enteral nutrition